2023
DOI: 10.3390/f14081638
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Transcriptome and Biochemical Analysis Provides New Insights into the Leaf Color Change in Acer fabri

Abstract: Acer fabri is a widely distributed ornamental tree with colorful leaves and high ornamental value. Its young leaves change from red to red and green until turning fully green. To understand the mechanism of leaf color change, transcriptome sequencing and pigment content determination were performed in three stages during the leaf color change of A. fabri. In total, 53,550 genes, including 838 transcription factors (TFs), were identified by transcriptome sequencing. In addition, the results of orthogonal partia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…With development, the anthocyanin content in the leaves gradually decreased and the carotenoid (lutein and zeaxanthin) and chlorophyll (chlorophyll a and chlorophyll b) contents gradually increased until, finally, the leaves appeared green. The results appear to be similar to previous studies [2].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…With development, the anthocyanin content in the leaves gradually decreased and the carotenoid (lutein and zeaxanthin) and chlorophyll (chlorophyll a and chlorophyll b) contents gradually increased until, finally, the leaves appeared green. The results appear to be similar to previous studies [2].…”
Section: Discussionsupporting
confidence: 92%
“…After transcriptome sequencing the different colors of Acer pseudosieboldianum leaves, 50,501 genes were identified [42]. A total of 53,550 genes were identified by transcriptome sequencing different colors of Acer fabri leaves and three key genes related to anthocyanin synthesis were identified [2]. We conducted transcriptome sequencing for six stages of leaf color changes of O. fragrans 'Wucaigui' and compared the results with the whole genome of O. fragrans.…”
Section: Discussionmentioning
confidence: 99%
“…In Arabidopsis, AtNAC087 overexpression induces anthocyanin accumulation, decreases chlorophyll content, and enhances the expression of leaf senescence-related genes. The expression of AfNAC083 is positively correlated with the anthocyanin content in Acer fabri [53]. IbNAC056a/b in sweet potato promotes anthocyanin accumulation [54].…”
Section: Discussionmentioning
confidence: 98%
“…Huang et al investigated the expression of circRNAs associated with the senescence process in rice rapeseed leaves and reported that 17 senescence-related circRNAs were predicted to have parental genes by weighted gene co-expression network analysis (WGCNA), of which regulation of their parental genes by three circRNAs was verified by qRT-PCR [ 62 ]. The expression of AfNAC083 in Acer fabri is positively correlated with anthocyanin content [ 63 ]. Our analysis of the DECs and their parental genes showed that the parental gene of novel_circ_003018 is gene-Qm012601 (NAC083), which is an important transcription factor regulating leaf colour in Q. mongolica .…”
Section: Discussionmentioning
confidence: 99%